Reminiscence sebagai Strategi untuk Meningkatkan Kesejahteraan Psikologis Lansia di Panti Jompo - Yuli Fatimatu Zahro; Mohammad Nur Ikhwan; Nihayatun Nikmah; Hilda Rizkiya Mahdani; Syafina El Qolbina; Tegar Valentino; Andina Nur Setyani; Rahma Syafa'Anisa; Fajar Indah Nuryanti; Siti Hikmah (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
Old age is a challenging phase of life, characterized by physical, social and psychological changes that often affect the emotional well-being of the elderly. Loneliness, loss of meaning in life, and prolonged stress are often experienced, especially by those living in nursing homes. One effective approach to overcome this is reminiscence therapy, which is an activity of remembering and retelling past experiences. This study uses a qualitative approach with phenomenological methods to explore how memories of youth can be a source of emotional strength for the elderly. In-depth interviews were conducted with several elderly people in nursing homes. The results revealed that reminiscing about the past had a positive impact on their psychological state. Three main themes were found: (1) memories of youth foster happiness and nostalgia, (2) life achievements foster a sense of pride and self-identity, and (3) life value is gained through social relationships, spirituality, and acceptance. This process strengthens the emotional resilience of the elderly and improves quality of life. Thus, reminiscing about the past is not just nostalgia, but an important psychosocial intervention. Reminiscence therapy is recommended to be implemented routinely as part of efforts to improve the mental well-being of older adults in nursing homes.